Strategi Komunikasi Pemasaran untuk Penguatan Urban Farming di Kelurahan Mangunsari, Kecamatan Gunungpati - Rekno Sulandjari; Dina Damayanti; Heru Sri Wulan; Leonardo Budi Hasiholan; Angel Maynanda Ayu Gracia Fani (Universitas 17 Agustus 1945 Semarang, 2025)
In the digital era, marketing communication must dynamically adapt to technological developments and shifts in consumer behavior. Social media, interactive content, and data-driven marketing have become essential components of modern strategies. Social media platforms not only serve promotional purposes but also enable direct engagement, feedback collection, and the strengthening of emotional connections with consumers. Visual content such as videos and photos of urban farming activities help expand outreach and raise public awareness. This study aims to analyze the marketing communication strategies that strengthen urban farming programs in Mangunsari Village, Salatiga City, using a qualitative approach. The findings reveal that urban farming actors actively utilize multiple communication platforms—both written and digital—to promote their initiatives. Key strategies include publishing features on digital platforms such as Kompasiana.com and optimizing social media to showcase cultivation and harvest activities. Furthermore, the support from local administrative officials plays a vital role in enhancing marketing communication efforts. Policy guidance and facilitation of interactions with external stakeholders create broader networking opportunities. This success story illustrates that a synergy between creative communication strategies and institutional support can effectively promote urban farming as a community-based solution for improving local welfare through the use of local wisdom.